Understanding zoonotic diseases - Romich, Janet Amundson (Thomson Delmar Learning, 2008)
(Publisher-supplied data) Understanding Zoonotic Diseases is written for both animal and human healthcare professionals and students that will help them understand specific zoonotic diseases. Designed as a stand-alone book, it introduces the reader to microbes including bacteria, fungi, parasites, viruses, and prions, and describes specific diseases that can be transmitted from animals to humans. Extensive use of images, photographs, tables, and clinically relevant comments helps the reader understand the role of animals in causing diseases in humans. Review questions at the end of each chapter and online critical thinking questions help the learner gain a deeper understanding of the material and aid in retention